Bioartificial heart: a human-sized porcine model : the way ahead - Weymann, Alexander; Korkmaz-İçöz, Sevil; Li, Shiliang; Veres, Gábor; Chaimow, Nicole; Pätzold, Ines; Czerny, Natalie; Schies, Carsten; Schmack, Bastian; Karck, Matthias; Szabó, Gábor (PLOS ONE, 2014)
Background: A bioartificial heart is a theoretical alternative to transplantation or mechanical left ventricular support. Native hearts decellularized with preserved architecture and vasculature may provide an acellular tissue platform for organ regeneration. We sought to develop a tissue-engineered whole-heart neoscaffold in human-sized porcine hearts. - Methods: We decellularized porcine hearts (n = 10) by coronary perfusion with ionic detergents in a modified Langendorff circuit. We confirmed decellularization by histology, transmission electron microscopy and fluorescence microscopy, quantified residual DNA by spectrophotometry, and evaluated biomechanical stability with ex-vivo left-ventricular pressure/ volume studies, all compared to controls. We then mounted the decellularized porcine hearts in a bioreactor and reseeded them with murine neonatal cardiac cells and human umbilical cord derived endothelial cells (HUVEC) under simulated physiological conditions. - Results: Decellularized hearts lacked intracellular components but retained specific collagen fibers, proteoglycan, elastin and mechanical integrity; quantitative DNA analysis demonstrated a significant reduction of DNA compared to controls (82.663.2 ng DNA/mg tissue vs. 473.2613.4 ng DNA/mg tissue, p,0.05). Recellularized porcine whole-heart neoscaffolds demonstrated re-endothelialization of coronary vasculature and measurable intrinsic myocardial electrical activity at 10 days, with perfused organ culture maintained for up to 3 weeks. - Conclusions: Human-sized decellularized porcine hearts provide a promising tissue-engineering platform that may lead to future clinical strategies in the treatment of heart failure.
Gesehen am 18.08.2020